2017
DOI: 10.1111/jcmm.13078
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac cell proliferation is not necessary for exercise‐induced cardiac growth but required for its protection against ischaemia/reperfusion injury

Abstract: The adult heart retains a limited ability to regenerate in response to injury. Although exercise can reduce cardiac ischaemia/reperfusion (I/R) injury, the relative contribution of cardiac cell proliferation including newly formed cardiomyocytes remains unclear. A 4-week swimming murine model was utilized to induce cardiac physiological growth. Simultaneously, the antineoplastic agent 5-fluorouracil (5-FU), which acts during the S phase of the cell cycle, was given to mice via intraperitoneal injections. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
1
24
0
1
Order By: Relevance
“…The protective effects of exercise against cardiac I/R injury have been well acknowledged [19, 31, 38, 50], which could be associated with reduced myocardial inflammation, minimized oxidative and nitric-oxidative stress, decreased cardiomyocyte apoptosis, and promoted angiogenesis. It was recently reported that exercise is able to enhance cardiomyocyte renewal [34, 42], which is necessary to mediate the protective effect of exercise against I/R injury [5]. Moreover, exercise is efficient to reduce cardiac I/R injury both at baseline and in obese diabetic condition, though different molecular mechanisms might be involved [9, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of exercise against cardiac I/R injury have been well acknowledged [19, 31, 38, 50], which could be associated with reduced myocardial inflammation, minimized oxidative and nitric-oxidative stress, decreased cardiomyocyte apoptosis, and promoted angiogenesis. It was recently reported that exercise is able to enhance cardiomyocyte renewal [34, 42], which is necessary to mediate the protective effect of exercise against I/R injury [5]. Moreover, exercise is efficient to reduce cardiac I/R injury both at baseline and in obese diabetic condition, though different molecular mechanisms might be involved [9, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Wheat germ agglutinin (WGA) staining was performed to show the contour and measure of cardiomyocyte size. 22,23 As shown in Taken together, these results suggested that knockdown of ln-cRNA MEG3 could inhibit cardiomyocyte hypertrophy, cardiomyocyte loss and cardiac fibrosis in the border zone following MI.…”
Section: The Effects Of Lncrna Meg3 Knockdown On Myocardial Infarctsupporting
confidence: 59%
“…Wheat germ agglutinin (WGA) staining was performed to show the contour and measure of cardiomyocyte size . As shown in Figure C, the staining results indicated that the hearts from MI group exhibited enlarged cardiomyocyte size and reduced cardiomyocyte number in border zone compared with those of the sham group at 4 weeks post‐MI.…”
Section: Resultsmentioning
confidence: 99%
“… 7 It has been found that injection of 5-fluorouracil inhibits cardiac cell proliferation and limits the exercised-induced cardioprotective effects from ischemia-reperfusion (I/R) injury without affecting the exercised-induced cardiac hypertrophy in vivo . 8
Fig. 1 Cardiac adaptations in response to exercise.
…”
Section: Cardiac Adaptation In Response To Exercisementioning
confidence: 99%